IMPROVING STUDENTS ABILITY IN READING COMPREHENSION HORTATORY EXPOSITION TEXT THROUGH COOPERATIVE INTEGRATED READING AND COMPOSITION - Mandasari, Novy Rianty; Arifin, Zainal; Riyanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstrak: penelitian ini adalah penelitian tindakan kelas (PTK) pada siswa kelas sebelas MA Negeri 02 Pontianak tahun ajaran 2011/2012. Penelitian ini bertujuan untuk mengetahui seberapa baik cooperative integrated reading and composition (CIRC) membantu siswa dalam memahami teks. Alat pengumpulan data dalam penelitian ini adalah lembar observasi, catatan lapangan, dan tes tertulis. Hasil data penelitian dianalisis menggunakan rubrik penilaian. Analisa tes siswa meliputi kemampuan siswa dalam menemukan ide pokok, gagasan pendukung, referensi, memahami kesimpulan dan kosa kata serta membuat ringkasan. Kemampuan siswa dalam memahami teks bacaan hortatory exposition meningkat dalam tiga siklus, dari 4,87 (pilihan ganda) dan 6,54 (esei) pada siklus pertama, kemudian meningkat pada siklus kedua, 7,72 (pilihan ganda) dan 4,55 (esei) dan mencapai 8,6 (pilihan ganda) dan 8,7 (esei) pada siklus ketiga. Kata kunci: cooperative integrated reading and composition (CIRC), teks hortatori eksposisi, memahami bacaan. Abstract: This study was a classroom action research (CAR) at eleventh grade students of MA Negeri 02 Pontianak in academic year 2011/2012. The aim of this research is to know how well cooperative integrated reading and composition (CIRC) help the students in reading comprehension. The tools of data collecting in this research were observation checklist, field note and writing test. Data was analyzed by using scoring profile. The analysis of students test result covered students ability in finding out the main idea, details, reference, understanding the inference and vocabulary and making the summary of text. The students ability in reading comprehension hortatory exposition text improved in three cycles, from 4.87 (multiple choice) and 6.54 (essay) in cycle 1, then improved in cycle 2, 7.72(multiple choice) and 4.55 (essay), up to 8.6 (multiple choice) and 8.7 (essay) in cycle 3. Keywords: cooperative Integrated Reading and Composition (CIRC), hortatory exposition text, reading comprehension.